Whole-exome sequencing identifies a novel mutation in spermine synthase gene (SMS) associated with Snyder-Robinson Syndrome - Qazi, Talal J. (BMC Med Genet, 2020)
BACKGROUND: Loss of function mutations in the spermine synthase gene (SMS) have been reported to cause a rare X-linked intellectual disability known as Snyder-Robinson Syndrome (SRS). Besides intellectual disability, SRS is also characterized by reduced bone density, osteoporosis and facial dysmorphism. SRS phenotypes evolve with age from childhood to adulthood. METHODS: Whole exome sequencing was performed to know the causative gene/pathogenic variant. Later we confirmed the pathogenic variant through Sanger sequencing. Furthermore, we also performed the mutational analysis through HOPE SERVER and SWISS-MODEL. Also, radiographs were also obtained for affected individual to confirm the disease features. RESULTS: In this article, we report the first Pakistani family consisting of three patients with SRS and a novel missense pathogenic variant in the SMS gene (c.905 C > T p.(Ser302Leu)). In addition to the typical phenotypes, one patient presented with early-onset seizures. Clinical features, genetic and in-silico analysis linked the affected patients of the family with Snyder-Robinson and suggest that this novel mutation affects the spermine synthase activity. CONCLUSION: A novel missense variant in the SMS, c.905C > T p. (Ser302Leu), causing Snyder- Robinson Syndrome (SRS) is reported in three members of Pakistani Family.